Exploring the Diversity and Metabolic Profiles of Bacterial Communities Associated With Antarctic Sponges (Terra Nova Bay, Ross Sea) - Papale, Maria; Rizzo, Carmen; Fani, Renato; Bertolino, Marco; Costa, Gabriele; Paytuví-Gallart, Andreu; Schiaparelli, Stefano; Michaud, Luigi; Azzaro, Maurizio; Lo Giudice, Angelina (Frontiers in Ecology and Evolution, 2020)
Complex cell-to-cell interactions (including the production of antibiotics and the quorum sensing phenomenon) occur between benthic marine organisms and bacteria, leading to the establishment of synergistic interactions, especially in extreme and harsh environments, such as Antarctica. Despite this, current data concerning the composition, host- and site-relatedness, and biotechnological values of the bacterial community associated with Antarctic sponges are limited to few works, resulting in a still fragmented and incomplete knowledge. In this context, a total of 11 sponge species (belonging to Demospongiae and Hexactinellida) from the Terra Nova Bay area (Ross Sea) were explored for the associated bacterial diversity by the ION Torrent sequencing. An additional predictive functional analysis on 16S rRNA gene data was performed to unravel metabolic and biotechnological potentials of the associated bacterial communities. Data obtained highlighted the predominance of Proteobacteria, mainly affiliated to Alpha- and Gammaproteobacteria. Retrieved phyla were similarly distributed across samples, with dissimilarities encountered for the sponge Haliclona (Rhizoniera) dancoi (Topsent, 1901). Functional prediction results suggested that the associated bacterial community may be involved in the biosynthesis of antibiotics, quorum sensing and degradation of aromatic compounds.